Equality Between Husband and Wife in Islamic Marriage Law Perspective of Sheikh Wahbah Zuhaili: Reinterpretation of Qiwamah and Nusyuz in the Framework of Gender Justice - Roza Anggraini; Illy Yanti; Abdul Halim (Suluah Pasaman, 2026)
This study examines the concept of equality between husband and wife in Islamic marriage law from the perspective of Sheikh Wahbah Zuhaili. The background of this study is the existence of diverse interpretations of the husband-wife relationship in the fiqh munakahat, which often gives rise to inequality of rights and obligations in household practices. The purpose of this study is to describe, analyze, and discover the construction of Wahbah Zuhaili's thoughts on gender equality in marriage. The method used is library research with a normative-philosophical approach. The primary data source refers to Wahbah Zuhaili's magnum opus, al-Fiqh al-Islāmī wa Adillatuhū, while secondary data comes from books, journals, and other relevant literature. The data analysis technique uses a descriptive-analytical method. The results of the study show that according to Wahbah Zuhaili, Islam basically places husband and wife in an equal position as human beings before God. Differences in roles in the household, such as the husband's leadership and the obligation to provide for, are functional and do not ignore the principles of justice and deliberation. Equality is interpreted as equality in dignity and rights, not absolute equality of roles. Wahbah Zuhaili emphasizes the concepts of mu‘āsyarah bil ma‘rūf, justice, and partnership as the foundations of marriage. The implication of this thinking is the importance of reinterpreting marital jurisprudence that is responsive to gender justice without abandoning the Islamic texts